Interpreting a cultural value: An examination of the Indigenous concept of non-interference in North America. (January 2019) - Wark, Joe; Neckoway, Raymond; Brownlee, Keith
This article examines the Indigenous cultural value of non-interference in North America, which is portrayed in the literature as a central influence on interpersonal interactions. The findings suggest that while Indigenous peoples prefer subtle forms of interpersonal influence that maintain respectful and nurturing relationships, non-interference is not, as sometimes portrayed, an overriding value that supplants all other considerations. This article highlights the need for cross-cultural perspectives and practices that challenge one-dimensional cultural presumptions.